Morphophysiological Differences between the Metapleural Glands of Fungus-Growing and Non-Fungus-Growing Ants (Hymenoptera, Formicidae) - Vieira, Alexsandro Santana [UNESP]; Bueno, Odair Correa [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Public Library Science, 2012)
The metapleural gland is an organ exclusive to ants. Its main role is to produce secretions that inhibit the proliferation of different types of pathogens. The aim of the present study was to examine the morphophysiological differences between the metapleural gland of 3 non-fungus-growing ants of the tribes Ectatommini, Myrmicini, and Blepharidattini and that of 5 fungus-growing ants from 2 basal and 3 derived attine genera. The metapleural gland of the non-fungus-growing ants and the basal attine ants has fewer secretory cells than that of the derived attine ants (leaf-cutting ants). In addition, the metapleural gland of the latter had more clusters of secretory cells and sieve plates, indicating a greater storage capacity and demand for secretion in these more advanced farming ants. The glands of the derived attine ants also produced higher levels of polysaccharides and acidic lipids than those of Myrmicini, Blepharidattini, and basal attines. Our results confirm morphophysiological differences between the metapleural glands of the derived attines and those of the basal attines and non-fungus-growing ants, suggesting that the metapleural glands of the derived attines (leaf-cutting ants) are more developed in morphology and physiology, with enhanced secretion production (acidic lipids and protein) to protect against the proliferation of unwanted fungi and bacteria in the fungal garden, it is possible that leaf-cutting ants may have evolved more developed metapleural glands in response to stronger pressure from parasites.